IRON LOCAL STRUCTURE IN TEKTITES AND IMPACT GLASSES BY EXTENDED X-RAY ABSORPTION FINE STRUCTURE AND HIGH-RESOLUTION X-RAY ABSORPTION NEAR-EDGE STRUCTURE SPECTROSCOPY - Giuli G.; Pratesi G.; Cipriani C.; Paris E. (My University, 2002)
The local structure of iron in three tektites has been studied by means of Fe K-edge extended X-ray absorption fine structure (EXAFS) and high-resolution X-ray absorption near-edge structure (XANES) spectroscopy in order to provide quantitative data on distance and Fe coordination number. The samples studied are a moldavite and two australasian tektites. Fe model compounds with known Fe oxidation state and coordination number were used as standards in order to extract structural information from the XANES pre-edge peak. EXAFS-derived grand mean distances and Fe coordination numbers for the three tektite samples are constant within the estimated error ( =2.00 Α +/- 0.02 Α, CN = 4.0 +/- 0.4). In contrast to other data from the literature on Fe-bearing silicate glasses, the tektites spectra could not be fitted with a single Fe-O distance, but rather were fit with two independent distances (2 x 1.92 Α and 2 x 2.08 Α). High-resolution XANES spectra of the three tektites display a pre-edge peak whose intensity is intermediate between those of staurolite and grandidierite, thus suggesting a mean coordination number intermediate between 4 and 5. Combining the EXAFS and XANES data for Fe, we infer the mean coordination number to be close to 4.5.Comparison of the tektites XANES spectra with those of a suite of different impact glasses clearly shows that tektites display a relatively narrow range of Fe oxidation state and coordination numbers, whereas impact glasses data span a much wider range of Fe oxidation states (from divalent to trivalent) and coordination numbers (from tetra-coordinated to esa-coordinated). These data suggest that the tektite production process is very similar for all the known strewn fields, whereas impact glasses can experience a wide variety of different temperature-pressure-oxygen fugacity conditions, leading to different Fe local structure in the resulting glasses. These data could be of aid in discriminating between tektite-like impact glasses and impact glasses sensu strictu.